MO592INTERLEUKIN-1A (IL-1A) IS A CENTRAL REGULATOR OF INFLAMMATION IN CARDIOVASCULAR AND KIDNEY DISEASES. (29th May 2021) - Schunk, Stefan; Sarah, Triem; Kramann, Rafael; Boor, Peter; Ampofo, Emmanuel; Fliser, Danilo; Speer, Thimoteus
Abstract: Background and Aims: Cardiovascular diseases (CVD) and chronic kidney disease (CKD) are highly prevalent, aggravate each other, and account for substantial mortality. Both conditions are characterized by activation of the innate immune system. The alarmin IL-1α is expressed in a variety of cell types promoting (sterile) systemic inflammation. The aim of the present study is to examine the role of IL-1α in mediating inflammation in the setting of cardiorenal diseases. Method: We assessed the expression of IL-1α on the surface of monocytes from patients with acute myocardial infarction (AMI) and patients with CKD and determined its association with atherosclerotic CVD events during follow-up in an explorative clinical study. Furthermore, we assessed the inflammatory effects of IL-1α in several organ injury models in Il1a -/- and Il1b -/- mice and investigated the underlying mechanisms in vitro in monocytes and endothelial cells. Results: IL-1α is strongly expressed on the surface of monocytes from patients with AMI and CKD compared to healthy controls. Higher IL-1α surface expression on monocytes from patients with AMI was associated with a higher risk for atherosclerotic CVD events, which underlines the clinical relevance of IL-1α. In mice, IL-1α, but not IL-1β, mediates leukocyte-endothelial adhesion as determined by intravital microscopy. IL-1α promotes accumulation of macrophages and neutrophils in inflamed tissue in-vivo . Furthermore, IL-1α on monocytes stimulates their homing at sites of vascular injury. A variety of stimuli such as free fatty acids or oxalate crystals induce IL-1α surface expression and release by monocytes, which then mediates their adhesion to the endothelium via IL-1 receptor-1. Besides, IL-1α promotes expression of the vascular cell adhesion molecule-1 (VCAM-1) on endothelial cells thereby fostering the adhesion of circulating leukocytes. IL-1α induces inflammatory injury after experimental AMI and abrogation of IL-1α prevents the development of CKD in oxalate or adenine-fed mice. Conclusion: IL-1α represents a key mediator of leukocyte-endothelial adhesion and inflammation in cardiorenal diseases. Inhibition of IL-1α may serve as a novel anti-inflammatory treatment strategy.